(untitled) (GEOMATE Journal, 2019)
It is widely recognized that the Kansai area will be attacked by a plate boundary type huge earthquake within these 30 years. When the earthquake happens, the ground with underground structure, like a tunnel, would be struck by severe liquefaction disasters. Therefore, we tried to analyze the ground behavior using LIQCA, which is well used for liquefaction analysis in Japan. The input earthquake motion is the seismic standard spectrum I which is commonly used in Japan. The ground has the underground structure, so we investigated not only the liquefaction phenomenon of the ground itself but also the behavior of the underground structure. Furthermore, we focused on the boundary condition between the tunnel and the adjacent ground. Three patterns are prepared for this boundary condition.First, the boundary condition between the tunnel and the ground is free in the vertical direction and fixed in the horizontal direction. Second, this boundary condition is fixed in the vertical direction and the horizontal direction is fixed. Third, the joint elements are installed between the tunnel and the ground. Under each condition, we examine the effect of liquefaction on the tunnel. Also, we compare the three patterns and verified realistic damage.